Perception of Business Ethics and Healthcare Service Quality in Hospitals: Impact on Patient Satisfaction and Loyalty - Widjaja, Trees Nia Sari; Sikki, Nurhaeni; Kasyati, Kasyati; Yinnie, Celine; Febrina, Dara Meutia Ayu; Kusyanto, Fahmi Abdullah; Hayya, Lidya Nur; Samsu, Ridha Aprillah; Astuti, Tri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the impact of patients' perceptions of business ethics and healthcare service quality on their satisfaction and loyalty within hospital settings. As healthcare becomes increasingly competitive, ethical conduct and service quality have emerged as pivotal factors in ensuring patient retention. A quantitative research approach was utilized, with data collected from 200 hospital patients through a structured questionnaire. The findings reveal a significant positive relationship between business ethics and service quality on patient satisfaction. Moreover, patient satisfaction was found to strongly influence patient loyalty. The results highlight the importance of ethical practices and high service quality as strategic drivers for enhancing patient loyalty. The study concludes by offering managerial recommendations aimed at fostering better ethical standards and improving healthcare service delivery to strengthen patient retention.